The Paradigm Shift? - Roşia Montană between Industrialization and Post-Industrialization - Ştefan-Sebastian, Maftei (International Journal of Industrial Engineering and Management, 2014)
The paper will try to argue that the Roşia Montană protest phenomenon in Romania is significant for two main reasons. First, that this protest movement may have changed the nature of civic involvement in post-Communist Romania, especially with reference to the levels of participation and the new participatory environments. Second, that the Roşia Montană civic phenomenon may have also contributed, directly or not, to the changing of the paradigm of thinking economic processes in post-communist Romania, from a developmental approach to a post-industrial approach. Article history: Received (08.01.2014); Revised (25.02.2014); Accepted (15.03.2014)